INTERNAL CORPORATE COMMUNICATION AS A PILLAR OF HOSPITAL GOVERNANCE: A SYSTEMATIC REVIEW OF BEST PRACTICES - Ricky Agusiady; Witri Cahyati; Adhyasa Henry Nugraha (PT Altin Riset Publishing, 2026)
This study investigates internal communication as a strategic pillar of hospital governance to enhance transparency, accountability, service quality, and patient safety. Using a PRISMA-guided systematic review, literature published between 2013 and 2023 was retrieved from Scopus, PubMed, ProQuest, and the Garuda Indonesia database. Out of 1,120 initial records, 5 studies met the inclusion criteria and were analyzed thematically. Findings reveal four key themes of best practice: information transparency and open leadership, two-way feedback and employee participation, digital technology utilization, and organizational culture that promotes psychological safety. These practices strengthen staff trust, improve incident reporting, reduce medical errors, and enhance emergency coordination through structured communication. The results demonstrate that internal communication is not merely an information channel but a critical mechanism for quality governance. This study provides theoretical insights and practical recommendations for hospitals particularly in Southeast Asia to integrate open, technology-driven communication as part of effective and sustainable governance policies.